The Biblical illustrator; or, Anecdotes, similes, emblems, illustrations: expository, scientific, georgraphical, historical, and homiletic, gathered from a wide range of home and foreign literature, on the verses of the Bible - Exell, Joseph S. (F. H. Revell, 1905)
1. Genesis. 2 v. -- 2. Exodus. -- 3. Leviticus. Numbers. 2 v. in 1. -- 5. Deuteronomy. -- 6. Joshua, Judges, Ruth. -- 9. I. Samuel. -- 10. II. Samuel. -- 11. I. Kings. -- 12. II. Kings. -- 13. First Chronicles. Second Chronicles. Ezra. Nehemiah. Esther. 5 v. in 1. -- 18. Job. -- 19. Psalms. 5 v. -- 20. Proverbs. -- 21. Ecclesiastes. The Song of Solomon. 2 v. in 1. -- 23. Isaiah. 3 v. -- 24. Jeremiah. The Lamentations of Jeremiah. 3 v. in 2. -- 26. Ezekiel. -- 27. Daniel. -- 28. The Minor prophets. 2 v. -- 40. Saint Matthew. -- 41. Saint Mark. -- 42. Saint Luke. 3 v. -- 43. St. John. 3 v. -- 44. The Acts. 3 v. -- 45. Romans. 2 v. -- 46. I. Corinthians. 2 v. -- 47. Second Corinthians. -- 48. Galatians. -- 49. Ephesisans. -- 50 . Philippians, Colossians. -- 52. I. Thessalonians. II. Thessalonians. I. Timothy. Titus, Philemon. -- 58. Hebrews. 2 v. -- 59. St. James. -- 60 . First Peter. Second Peter. 2 v. in 1. -- 62. First John. Second Peter. 2 v. in 1. -- 62. First John. Second John. Third John. Jude. 4 v. in 1. -- 66. Revelations. -- 67. Index to the New Testament volumes, composed by T. F. Peachey.